2008
DOI: 10.1002/jbm.b.31131
|View full text |Cite
|
Sign up to set email alerts
|

Biaxial flexure strength and low temperature degradation of Ce‐TZP/Al2O3 nanocomposite and Y‐TZP as dental restoratives

Abstract: The purpose of the present study was to evaluate the mechanical durability of a zirconia/alumina nanocomposite stabilized with cerium oxide (Ce-TZP/Al(2)O(3) nanocomposite) in comparison to yttria-stabilized tetragonal zirconia polycrystals (Y-TZP) and discuss its application on ceramic dental restorations. The disk-shaped specimens of both materials were stored in physiological saline solution at 80 degrees C for 30 days, in 4% acetic acid at 80 degrees C for 30 days, and in an autoclave at 121 degrees C for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
105
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(119 citation statements)
references
References 38 publications
6
105
1
2
Order By: Relevance
“…Disappearance of alumina phase In the present study, the Ce-TZP/Al2O3 nanocomposite was composed of 10 mol% CeO2 stabilized TZP as a matrix and 30 vol% of Al2O3 as a second phase. In our previous study 6) , it was reported that the average grain size of both phases was 0.49±0.12 µm. After a separate determination of each phase, the grain sizes of Ce-TZP and Al2O3 were 0.59±0.09 µm and 0.42±0.08 µm Table 1 Average X-ray intensity ratios of oxygen, zirconium, yttrium, hafnium, aluminum, and cerium in the irradiated pits to the surface composition without irradiation respectively.…”
Section: Effect On Surface Changesmentioning
confidence: 81%
See 1 more Smart Citation
“…Disappearance of alumina phase In the present study, the Ce-TZP/Al2O3 nanocomposite was composed of 10 mol% CeO2 stabilized TZP as a matrix and 30 vol% of Al2O3 as a second phase. In our previous study 6) , it was reported that the average grain size of both phases was 0.49±0.12 µm. After a separate determination of each phase, the grain sizes of Ce-TZP and Al2O3 were 0.59±0.09 µm and 0.42±0.08 µm Table 1 Average X-ray intensity ratios of oxygen, zirconium, yttrium, hafnium, aluminum, and cerium in the irradiated pits to the surface composition without irradiation respectively.…”
Section: Effect On Surface Changesmentioning
confidence: 81%
“…For improved mechanical strength, a ceriastabilized zirconia/alumina nanocomposite (Ce-TZP/ Al2O3 nanocomposite) was developed 3) . Previously, we demonstrated that, in comparison with Y-TZP, the Ce-TZP/Al2O3 nanocomposite exhibited a higher flexural strength and toughness, coupled with satisfactory durability, when exposed to low-temperature aging degradation in the various aqueous environments commonly encountered in dentistry [4][5][6] . Prosthetic devices are often complex in shape.…”
Section: Introductionmentioning
confidence: 98%
“…The tetragonal form for metastable zirconia in biomedical applications could be achieved at room temperature by alloying zirconia with other oxides (stabilizers), e.g. CaO [3], MgO [4], Y 2 O 3 [5][6][7][8] and CeO 2 [9]. Y 2 O 3 (approximately 3 mol%) is the most widely used stabilizer for dental zirconia (Y-TZP) [2].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many dental application of zirconia has been developed. 4,5) 3 mol%Y 2 O 3 stabilized tetragonal zirconia polycrystal (3Y-TZP) is the most popular material in such zirconia bioceramics, but some composites or doped-materials are also used in recent years. For example, alumina-dispersed ceria stabilized TZP with small amount of titania is developed in dental application.…”
Section: Introductionmentioning
confidence: 99%
“…For example, alumina-dispersed ceria stabilized TZP with small amount of titania is developed in dental application. 5) We have also developed an insert material for joining of zirconia dental bridge with a composition of 7.7 mol%TiO 2 -doped TZP, 6,7) by applying enhanced superplasticity in TiO 2 -doped TZP explained from the balance between the grain size and the increased accommodation length for the stress concentration by diffusion. [8][9][10] Thus, it is important to investigate the effect of second phase or dopant on some properties in zirconia bioceramics.…”
Section: Introductionmentioning
confidence: 99%